Tindak Pidana Politik Uang di Indonesia Pada Saat Pemilu Perspektif Fiqh Jinayah dan Hukum Positif - M. Husni Mubarok (Rechtenstudent, 2021)
Elections are important in a democracy that adheres to a representative system to determine a state leader, especially Indonesia, whose leadership system is presidential or also known as the congressional system. The function of elections is to act as a filter for "politicians" who will represent and bring the people's voice in representative institutions, those who are elected are considered as people or groups who have the ability or obligation to speak and act on behalf of a larger group through parties. politics (political parties). Therefore, the existence of political parties is a must in modern democratic political life. Gifts that come from state officials are no stranger to whether it be in the form of financial or goods assistance, one of the goals is none other than imaging, which is done openly in order to give a good image in front of the general public. The issue of money politics always appears in democratic events. Both at the village, district, city, provincial, and national levels. The emergence of money politics is due to the fact that people are still tolerant and permissive of money politics. The public considers money politics as a sustenance that cannot be denied, as an addition to daily needs, as a cost or compensation for the contestants. Because on election day they do not work, go to the fields, or the fields. So that money politics is considered as an opportunity to get fortune.